Bromatological study Rosmarinus officinalis L. “romero” and obtention of its essential oil - Ponce, Julio (2015)
It was obtained the essential oil from fresh and dehydrated leaves of plant specie Rosmarinus officinalis L. "romero" from Huaraz (Ancash), Huancayo and Lima, with the purpose of determining if the species cultivated, harvested in the time of flowering and post flowering, meets the international standards such as herb flavor. Dehydration was carried out in air circulating oven at 38°C for 48 hours. For the proximal analysis were used methods of OMA of AOAC international (2011). The essential oil was carried out by extraction method of volatile oils draggable by vapor stream. The results obtained in fresh and dehydrated sample in g% were, respectively, humidity (gravimetric method) 62,41 and 18,82; (azeotropic method) 60,50 and 16,20; total ash 2,34 and 5,44; acid insoluble ash 0,16 and 0,15; proteins 4,68 and 5,32; carbohydrates 20,61 and 45,05; fiber 4,52 and 14,62; fat 7,35 and 13,37; ascorbic acid (mg%) 59,20 and 58,66; essential oil obtained (mL in 100 g) 0,36 and 0,35. The ash and carbohydrates content were found in accordance with international standards, while proteins and fats were above and the content of essential oil obtained was below these standards. Borneol, found by thin-layer chromatography, indicated that the sample has commercial quality.